1991
DOI: 10.1021/bi00219a021
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of cytochrome c2 with photosynthetic reaction centers from Rhodopseudomonas viridis

Abstract: The reactions of Rhodopseudomonas viridis cytochrome c2 and horse cytochrome c with Rps. viridis photosynthetic reaction centers were studied by using both single- and double-flash excitation. Single-flash excitation of the reaction centers resulted in rapid photooxidation of cytochrome c-556 in the cytochrome subunit of the reaction center. The photooxidized cytochrome c-556 was subsequently reduced by electron transfer from ferrocytochrome c2 present in the solution. The rate constant for this reaction had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 47 publications
(68 reference statements)
8
54
1
Order By: Relevance
“…Its reduction potential (ϩ350 mV) is typical of cytochromes c 2 , and our experiments with purified protein and membrane fragments show that the electron transfer rate from cytochrome c 2 to the reaction center is within the range found in other purple bacteria (8,32). A cycA mutant was unable to grow phototrophically, indicating that cytochrome c 2 is the dominant donor to the reaction center during photosynthetic growth and that neither HiPIP can take on this role.…”
Section: Discussionsupporting
confidence: 49%
“…Its reduction potential (ϩ350 mV) is typical of cytochromes c 2 , and our experiments with purified protein and membrane fragments show that the electron transfer rate from cytochrome c 2 to the reaction center is within the range found in other purple bacteria (8,32). A cycA mutant was unable to grow phototrophically, indicating that cytochrome c 2 is the dominant donor to the reaction center during photosynthetic growth and that neither HiPIP can take on this role.…”
Section: Discussionsupporting
confidence: 49%
“…It has been shown that electron transfer reactions from soluble electron donors to the cytochrome subunit are controlled by charge interactions (12,13). The study of site-directed mutagenesis in R. gelatinosus has shown that negatively charged amino acids (Glu) surrounding the heme-1 (positions 82, 113, and 129 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the following properties of the subunit have been shown: 1) the four hemes are arranged sequentially with high-low-high-low midpoint potentials; 2) the subunit can reduce the photo-oxidized special pair of bacteriochlorophylls faster than the soluble cytochromes; and 3) the heme-1 of the cytochrome is a site involved in the electron flow from soluble electron carriers, indicating that all four hemes of the subunit are likely to be involved in electron transfer toward the photooxidized special pair of bacteriochlorophylls (12,13). The existence of a cytochrome subunit containing only three hemes, including one unusual heme in R. sulfidophilum, suggests that all four hemes and the arrangement of high-low-high-low midpoint potentials are not essential requirements for the functions of the subunit.…”
Section: Discussionmentioning
confidence: 99%
“…The electron transfer function and characterization of hemes in the cytochrome subunit has been widely studied in various purple bacteria (e.g, R. viridis [2][3][4][5][6][7][8][9][10][11][12], Rhodospirillum molischianum [13], Rubrivivax gelatinosus [14][15][16], Rhodof erax fermentans [17], Chromatium vinosum [18], and Rhodopseudomonas acidophila [19]). These studies have presented that the four hemes in the cytochrome subunit differ in redox midpoint potentials (Em) and peak wavelengths of the a-absorption bands, as shown in a recent review by Nitschke and Dracheva *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%